"The Food Matches the Mood": Experiences of Eating Disorders in Bipolar Disorder. (January 2021) - McAulay, Claire; Dawson, Lisa; Mond, Jonathan; Outhred, Tim; Touyz, Stephen
Approximately 33% of those with bipolar disorder (BD) have a comorbid eating disorder (ED). However, the trajectory of these conditions has received little research attention. Nine participants who met criteria for BD and an ED participated in qualitative interviews exploring experiences of illness onset, the interaction of these conditions, and service provision. Almost all participants in the sample reported minimal to no screening of ED problems, despite their health professionals' frequent discussion of obesity. Findings suggested that ED features were diverse and evolved over time. Mania and depression were connected to ED features such as overeating and restricting, but this differed between and within participants. Most participants disclosed historic trauma which they considered central to their mental health concerns. This clinical group appears to be underserviced. Clinicians and researchers should routinely screen for ED features when treating and diagnosing BD to inform their physical and mental health interventions.